Corporeality : emergent consciousness within its spatial dimensions - Öztürk, Maya Nanitchkova (Consciousness, literature & the arts, 2014)
Corporeality: Emergent consciousness within its spatial dimensions develops our understanding of what we can experience through our bodies in relation to the space around us. Rather than considering architecture as being about manifestation and mediation of fixed meanings, the book focuses instead on architectural space as a field that envelopes us incessantly, intimately, and affectively. We are in immediate contact with that space, and the way we relate to it determines how we are able to grasp the realities of the social and material worlds around us. This enquiry considers architectural spa.